Marvellous Paint Services Enterprise / Roziamril Sheikh Zain ... [et al.] - Ibrahim, Mohd Muslim; Shekh Zain, Roziamril; Saad, Mohd Fizal; Mansor, Arman Faizul; Ariffin, Yusof (2001)
Marvellous Paint Service Enterprise is fully other races in the country have monopolized Bumiputera Company that is trying to venture in the business of paint ervicing that. As a developing country, Malaysia provides many facilities and opportunities especially for bumiputera for becoming entrepreneurs. As a Malaysian Citizen, who will go through the era of globalization with the stable economic, political and social condition, we should take the challenge given toward us. Every participations from all the Malaysian in formed of energy and time will show to the world that Malaysia has proudly proved that we had been successful in the development. Due to this, we had taken some meaningful steps by making an initiative to formed a company by the name of Marvellous Paint Service Enterprise which provide services to paint and design a mixture of paint colors for houses and buildings or even offices. We choose this business because we knew that it has a bright futures and high potential to make profit and will expend successfully with the future demands of Malaysian citizen. As we can see, nowadays Malaysian are very modern in the way of their thinking and always think of a better home living environment as part of their need in life